2017
DOI: 10.15520/ijnd.2017.vol7.iss3.197.12-20
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students' Perception and Educational Needs regarding Nursing informatics

Abstract: nursing informatics is a new specialty in Egypt. It is becoming an important and integral part of healthcare organizations, it affects nursing outcome and quality of health care. Therefore, involving informatics basic knowledge and skills within a nursing education program is recommended to meet the future challenging trends that globally affect nursing workforce. Aim of the study: To assess nursing students' perception and educational needs regarding nursing informatics . Research Design: Descriptive Cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The high ratings for computer literacy skills, and specifically the high ratings for the use of Word processing, were likely because of the use of Word processing and computers for educational tasks during their training and the use of social media and email to communicate socially and educationally. This is also confirmed in other studies where students are reported to commonly make use of smart phone technologies and computers at home, communicate daily via email, the Internet and social media platforms, complete assignments through the (Elewa & El Guindy 2017). Telecommunication tools such as email, facsimiles (fax), WhatsApp groups and Zoom meetings are also used commonly in hospitals, making it possible that exposure of respondents to these skills in the clinical environment may also have enhanced their perceived relevance of these skills (Vasuki 2016).…”
Section: Computer Literacysupporting
confidence: 81%
“…The high ratings for computer literacy skills, and specifically the high ratings for the use of Word processing, were likely because of the use of Word processing and computers for educational tasks during their training and the use of social media and email to communicate socially and educationally. This is also confirmed in other studies where students are reported to commonly make use of smart phone technologies and computers at home, communicate daily via email, the Internet and social media platforms, complete assignments through the (Elewa & El Guindy 2017). Telecommunication tools such as email, facsimiles (fax), WhatsApp groups and Zoom meetings are also used commonly in hospitals, making it possible that exposure of respondents to these skills in the clinical environment may also have enhanced their perceived relevance of these skills (Vasuki 2016).…”
Section: Computer Literacysupporting
confidence: 81%
“…Other studies support this nding, as higher con dence levels in basic computer skills were reported among Baccalaureate-nursing students, associated with frequent computer use during the learning process [21,22,23]. Another study documented that most nursing students entering nursing programmes are computer literate, which could contribute to higher computer competence levels [24]. However, competence levels declined when basic computer skills were applied to practical experiences [20], as undergraduate nursing students rarely use ICT applications in clinical practice [24].…”
Section: Discussionmentioning
confidence: 74%
“…Another study documented that most nursing students entering nursing programmes are computer literate, which could contribute to higher computer competence levels [24]. However, competence levels declined when basic computer skills were applied to practical experiences [20], as undergraduate nursing students rarely use ICT applications in clinical practice [24]. Furthermore, the focus on developing basic computer skills seem to correlate with low NI implementation in undergraduate nursing curricula in Africa [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The utilisation of computers and technology in healthcare has expanded beyond human resources, financial, and logistics systems. It now encompasses clinical communications and the storage of patients' historical data, physicians' orders, laboratory results, and computerised nursing care plans (Elewa & El Guindy, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%